Aspergillus terreusstrain improvement for enhanced lovastatin production - Babot, Jaime Daniel (2015)
Cholesterol plays a vital role in body metabolism and membrane transport, and acts as precursor for the synthesis of several key biomolecules. Nevertheless, changes in cholesterol level lead to cardiovascular disorders, like atherosclerosis and hypercholesterolemia, which are currently the maincauses of death. This is why controlling cholesterol by inhibition of its biosynthesis is a promising approach. Cholesterol is synthetized from acetyl-CoA through a complex pathway, where the rate-limiting step is the conversion of HMG-CoA to mevalonate, catalyzed by HMG-CoA reductase.This key enzyme is selectively and competitively inhibited by lovastatin, a fungal secondary metaboliteused as a hypocholesterolemic which can therefore reduce the risk of cardiovascular diseases.